bahasa inggris - Margaretha Berek; Johan Andoyo Effendi Noor; Unggul Pundjung Juswono; Alfian Khoiri Anto; Sigma Nur Rismawati; Ayu Hardianti Pratiwi; Karimah Karimah; Fatimah Kunti Hentihu (Jurnal Penelitian Pendidikan IPA, 2022)
Research has been carried out on Measuring and Determining the Output Factors of 6 and 10 MV WFF photon beams in Small Square and Rectangular fields using Semiflex TM 31010 and PintPoint TM 31014 Ionization Chamber. This study aims to determine the value of the small field output factor. Measurements were carried out in a water phantom at a depth of 10 cm with a 100 cm SSD technique. The area of ​​the irradiation field used is (2 × 2; 3 × 3; 4 × 4; 2.5 × 1.6; 3.6 × 2.5; 4.5 × 2; and 5 × 3.2) cm2. Field output factor calculations were performed using the IAEA TRS. 483 dosimetry protocol. The results of measurements and calculations obtained for the two detectors used show that a decrease in the value of the output factor occurs when the field size is getting smaller. The output factor value in a small rectangular field looks smaller when compared to the output factor value in a small square field.